Does the participation in CSR activities enhance information diffusion? Evidence from US firms - Muhammad Suhail Rizwan; Asfia Obaid; Dawood Ashraf (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
The purpose of this paper is to investigate the impact of corporate social responsibility (CSR) on firm-specific information diffusion from 1,219 non-financial US firms between 2000 and 2012. By using Arellano-Bond dynamic panel-data estimation, we found evidence that suggests that stock prices of socially responsible firms have higher levels of firm-specific information diffusion. However, the size of firms plays a negative moderating role in this relationship. There is a positive and significant relationship between primary (technical) CSR activities and information diffusion among larger firms, while this relationship is reversed for secondary (institutional) CSR activities for similar firms. This study contributes to existing literature by providing empirical evidence on the CSR-Informativeness relationship, the moderating role of firm size and identifying the importance of primary stakeholders' CSR in US firms. This study has important policy implications for company management as it provides legitimacy to their CSR engagements, and to investors that CSR engagements should be considered as pricing factor.
Keywords: 330; corporate social responsibility; stock price informativeness; principal component analysis; market efficiency; dynamic panel model